Origins of the Bill of Rights - Levy, Leonard W. (Leonard Williams), 1923-2006 (Contemporary law series., 1999)
In this history of the origins of the Bill of Rights, Pulitzer Prize-winning historian Leonard W. Levy offers a panoramic view of the liberties secured by the first ten amendments to the Constitution. Levy illuminates the behind-the-scenes maneuverings, public rhetoric, and political motivations of James Madison and others who overcame fierce opposition to ensure the ratification of these crucial liberties.